The Greeks and Romans in the Black Sea and the importance of the Pontic region for the Graeco-Roman world (7th century BC-5th century AD) : 20 years on (1997-2017) : proceedings of the Sixth International Congress on Black Sea Antiquities (Constanţa - 18-22 September 2017) : dedicated to Prof. Sir John Boardman to celebrate his exceptional achievements and his 90th birthday - Boardman, John, 1927-; Tsetskhladze, Gocha R.,; Avram, Alexandru,; Hargrave, James (Archaeologist), (Archaeopress Archaeology, 2021)
This publication presents the Proceedings of the Sixth International Congress on Black Sea Antiquities, dedicated to the 90th birthday of Prof. Sir John Boardman, President of the Congress since its inception.